2020
DOI: 10.1016/j.phro.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of measures for assessing time-saving of automatic organ-at-risk segmentation in radiotherapy

Abstract: Background and purpose: In radiotherapy, automatic organ-at-risk segmentation algorithms allow faster delineation times, but clinically relevant contour evaluation remains challenging. Commonly used measures to assess automatic contours, such as volumetric Dice Similarity Coefficient (DSC) or Hausdorff distance, have shown to be good measures for geometric similarity, but do not always correlate with clinical applicability of the contours, or time needed to adjust them. This study aimed to evaluate the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
128
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 23 publications
5
128
1
Order By: Relevance
“…Although it was expected that DLC would stop contouring at this point, it was also expected that manual adjustment would occur here depending on the PTV extent. DLC might be improved by contouring the whole spinal cord, as it is generally easier to delete than add [22] . However, such analysis would still demonstrate adjustment is required here as the guidelines accept some variation in where to stop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was expected that DLC would stop contouring at this point, it was also expected that manual adjustment would occur here depending on the PTV extent. DLC might be improved by contouring the whole spinal cord, as it is generally easier to delete than add [22] . However, such analysis would still demonstrate adjustment is required here as the guidelines accept some variation in where to stop.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have shown, variability in contouring does not result in significant dosimetric differences for the majority of organs [4] , [24] . A threshold for meaningful contour adjustments could possibly be set [22] , and RTTs trained to accept contours in cases not exceeding this threshold. Practical tools to guide the user in this decision-making process will enable further automation of contouring practice.…”
Section: Discussionmentioning
confidence: 99%
“…It would be good to benchmark the measures, because while DSC is reasonably straightforward, HD results can be influenced substantially by the calculation algorithm. It would be good to include surface DSC [24] and/or Added Path Length [25] , as these measures are a surrogate for the potential time saving of DLC in comparison to manual delineation. Valentini et al [2] recommended to evaluate time saving, together with an assessment of dosimetric impact.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some CIs used here are mathematically correlated, using them together does not impact upon a model’s ability to make predictions of new observations on unseen data [25] and helps increase model complexity to reduce the likelihood of underfitting. Alternatively, the use of other types of mathematical metrics, such as the surface DSC [26] and added path length [27] , could be investigated to determine their suitability for this purpose.…”
Section: Discussionmentioning
confidence: 99%